Between reality and fiction : literary ekphrasis in Pedro Gómez Valderrama´s “El engañoso cuadro” (2012)
A panoramic exam toward Pedro Gómez Valderrama´s literary work, suggest a sporadic reference to the visual art. However a detailed assessment of it allows us to perceive that the writer set out in his writings a genuine look on the road to the art conside